A Real-World Data Driven Pharmacovigilance Investigation on Drug-Induced Arrhythmia Using KAERS DB, a Korean Nationwide Adverse Drug Reporting System - Go, Chaerin; Kim, Semi; Kim, Yujin; Sunwoo, Yongjun; Eom, Sae Hyun; Yun, Jiseong; Shin, Sooyoung; Choi, Yeo Jin (Pharmaceuticals, 2023)
This study aims to investigate the prevalence and seriousness of drug-induced arrhythmia and to identify predictors associated with the seriousness of arrhythmia. Drug-induced arrhythmia cases reported to the Korean Adverse Event Reporting System Database (KAERS DB) from January 2012 to December 2021 were investigated. A disproportionality test was performed to detect the association of the etiologic medication classes and types, along with patient demographic information, with the seriousness of drug-induced arrhythmia. Logistic regression was performed to investigate the predictors that increase the risk of serious arrhythmia. The most common etiologic agent for drug-induced arrhythmia was sevoflurane, whereas serious arrhythmia was most prevalent with narcotics. Antibiotics (reporting odds ratio (ROR) 4.125; 95% CI 1.438–11.835), chemotherapy (ROR 6.994; 95% CI 2.239–21.542), and iodinated contrast media (ROR 8.273; 95% CI 3.062–22.352) had a strong association with the seriousness of drug-induced arrhythmia. Among numerous etiologic agents, ioversol (ROR 16.490; 95% CI 3.589–75.772) and lidocaine (ROR 12.347; 95% CI 2.996–50.884) were more likely to be reported with serious arrhythmia. Aging and comorbidity, primarily cancer, are the most contributing predictors associated with serious arrhythmia. Further studies on the clinical significance of patient-specific predictors for the increased risk of serious drug-induced arrhythmia are warranted to promote drug safety.
Keywords: adverse drug events; arrhythmia; drug safety; KAERS DB; pharmacovigilance; RWD